The Effect of Supply Chain Management on the Operational Performance of Small and Medium Industries for Amplang Products in Samarinda City - Maryam Nadi; Asnawati Asnawati; Wirasmi Wardhani; Denny Maulida; Made Setini (International Journal of Supply Chain Management, 2020)
Industry is an economic activity which processes raw materials, semi-finished goods or finished materials into something that has fine use value as well as aesthetic value. Industries which are developing in Indonesia, both small and medium scale industries, make producers competing to produce a competitive product. Small and medium industries (IKM), amplang producers, compete to produce a competitive product. The population in this study were 13 business owners and employees of the IKM amplang producers. The research sample consisted of 30 respondents who are owners and employees of the amplang industry in Samarinda city. This study used Smart Partial Least Square (PLS) data analysis. The purpose of this study is to examine the effect of information sharing, long term relationship, and integration process on operational performance of amplang producers in Samarinda city. This research has succeeded in finding a positive and significant influence of information sharing on the operational performance of IKM amplang producers, long term relationships have a positive but insignificant effect on the operational performance of IKM amplang producers, and the integration process has a positive and significant effect on operational performance of amplang producers.